Die ondraaglike groenheid van teorie1 - Viljoen, Hein (Koers, 1993)
This article is a demonstration of the unbearable greenness of theory. The first part explores the meaning of green (in Afrikaans) as a demonstration of what intertextuality means. The second part outlines the resistance to theory. Against this resistance it is argued that theory is engaged (inter alia) in reading and interpreting difficult texts and contributing to solving the universal problem of interpretation. As an example the controversial singing of "Die Stem" at a rugby test is analyzed. The third part argues for the fecundity of theory by outlining the value of narrative theory for other disciplines and by a literary analysis of the science policy and the motto of the PU for CHE and a love poem by B. Breytenbach. A short programmatic view of the future of literary theory at the PU for CHE concludes the article.